Chinese Geographical Science - Fu, Bojie; Shang, Lina.; Luo, Ling.; Zhang, Chunli; Shang, Lina.; SpringerLink (Online service) (Heidelberg : Science Press : Imprint: Science Press, co-published with Springer.)
Chinese Geographical Science is an international journal, sponsored by Northeast Institute of Geography and Agroecology, Chinese Academy of Sciences, and published by Science Press, Beijing, China. Chinese Geographical Science is devoted to leading scientific and technological innovation in geography, serving development in China, and promoting international scientific exchange. The journal mainly covers physical geography and its sub-disciplines, human geography and its sub-disciplines, cartography, remote sensing, and geographic information systems. It pays close attention to the major issues the world is concerned with, such as the man-land relationship, population, resources, environment, globalization and regional development. The journal publishes original research papers, review articles, research reports, academic activities, and so on. All papers are subject to peer review and are published online at www.SpringerLink.com. .
Keywords: Geography; Geography, general